Signature-tagged transposon mutagenesis identifies novel mycobacterium tuberculosis genes involved in the parasitism of human macrophages - Rosas-Magallanes, Vania; Stadthagen-Gomez, Gustavo; Rauzier, Jean; Barreiro, Luis B.; Tailleux, Ludovic; Boudou, Frédéric; Griffin, Ruth; Nigou, Jérome; Jackson, Mary; Gicquel, Brigittte; Neyrolles, Olivier (ASM Press, 2007)
Using signature-tagged transposon mutagenesis, we isolated 23 Mycobacterium tuberculosis mutants, corresponding to 21 genes or genetic regions, attenuated in their ability to parasitize human macrophages. Mutants disrupted in the ABC transporter-encoding genes Rv0986 and Rv0987 were further characterized as being impaired in their ability to bind to host cells.